solve equation for x. if the equation has a solution that is in terms of other variables state any restriction on those variables

At first, we must simplify the two sides
[tex]4x-2(3-x)=2(x-3)+4x[/tex]Multiply the brackets by the numbers before them
[tex]\begin{gathered} 4x-2(3)-2(-x)=2(x)-2(3)+4x \\ 4x-6+2x=2x-6+4x \end{gathered}[/tex]Now, add the like terms on each side
[tex]\begin{gathered} (4x+2x)-6=(2x+4x)-6 \\ 6x-6=6x-6 \end{gathered}[/tex]Since the two sides have the same terms
Then this equation has many solutions (x can be any value)